Análise da qualidade da educação infantil em creches públicas municipais: uma comparação entre unidades próprias e conveniadas - Albuquerque, Bruno Feijó (2024)
Investment in education during early childhood is essential for the development of skills and abilities that are established in the first stages of basic education. It is crucial to highlight that enrollment in daycare centers for children aged 0 to 3 is optional, at the discretion of parents and caregivers; however, for children aged 4 and 5, participation in preschool is mandatory. According to current legislation, this stage can be offered by both the public and private networks, with the public network consisting of its own or partner units. In this context, the present study aims to carry out an exploratory analysis of the quality of education in affiliated daycare centers in comparison with its own units in a large city in the northeast region. The results show that the quality offered by municipal daycare centers is superior to that of partner daycare centers.